Effects of a pelletized mash containing fresh Asparagopsis taxiformis ‘brominata’ and oil on the performance of Holstein dairy cows - Isabela Fonseca Carrari; Valerie Annabelle Achziger; Nathalia Veloso Tropia; Dhones Rodriguez de Andrade; Marcos Inacio Marcondes (PLoS ONE, 2025)
Enteric methane emissions from ruminants are a major environmental concern, and the use of Asparagopsis taxiformis has been proposed as a mitigation strategy. However, its effects on dry matter intake (DMI) and overall animal performance require further investigation. This study evaluated the impact of Brominata® pellets, a high-bromoform, low-iodine Asparagopsis taxiformis product, on the DMI, digestibility, milk production and composition, and feed efficiency of lactating Holstein cows. Twelve lactating Holstein cows (254 ± 54.2 days in milk) were assigned to one of two treatments: a control pellet or the Brominata® pellet. The study lasted 23 days, including a 7-day adaptation period, an 8-day ramp-up phase, and 8 days of full-dose feeding (0.25% DM). Cows were housed individually and provided with a total mixed ration and water. DMI was measured daily, and sorting behavior was assessed to determine if there was particle selection against the pellet. Milk yield was recorded electronically, and milk samples were collected during the last three days and analyzed for composition. Digestibility was evaluated using spot fecal collection during the last three days of trial. Data were analyzed using a randomized block design, with repeated measures applied where appropriate. Results indicated no significant differences in DMI, milk yield, or feed efficiency between treatments. Daily intake fluctuations were observed but were consistent across treatments, suggesting that environmental or random farm effects influenced intake rather than the inclusion of Brominata®. Sorting analysis showed no evidence of cows selectively avoiding or preferring the Brominata® pellets, indicating good palatability. Digestibility analyses revealed a significant reduction in fat digestibility in cows fed Brominata® ( P = 0.046). Despite a reduction in fat digestibility, milk composition, including fat, protein, lactose, and solids non-fat, remained unaffected. In conclusion, including Brominata® pellets in the diet of lactating Holstein cows demonstrates no compromising effects on intake, milk production and composition, or feeding behavior.